Realization of fluorescence color tuning for poly(p-phenylenevinylene) coated microspheres via a heterogeneous catalytic thermal elimination process. Issue 9 (18th December 2014) - Chen, Yun; Qiu, Tian; Zhao, Wei; Fan, Li-Juan
Abstract : Fluorescent microspheres with clear core–shell structures and various emission colors were successfully prepared via a catalytic elimination process. Abstract : Poly( p -phenylenevinylene) (PPV) fluorescent microspheres were prepared in two steps. First, the positive sulfonium-salt PPV precursor (pre-PPV) was coated onto the surface of negatively charged polymer substrate spheres; second, the pre-PPV was converted into fluorescent PPV via a heterogeneous catalytic thermal elimination process. A series of fluorescent microspheres were obtained with different apparent colors and different fluorescence emissions simply by varying the elimination temperature. A spectroscopy study showed that, compared to the direct solid elimination, the spheres obtained via catalyzed elimination gave a very large variation in the emission, such as a larger shift in the wavelength, and more delicate spectra profiles with peaks and shoulders. Overlapping of the signals from blue channels and green channels in the confocal microscopy study gave a direct view of the gradual change from the blue emission to the green emission for the spheres obtained at elimination temperatures from 40 °C to 120 °C. Flow cytometry measurements showed that spheres obtained at different temperatures exhibit different combinations of the intensities from four different receiving channels. These PPV spheres were also demonstrated to have a smooth surface, monodispersity, a clear core–shell structure, thermal stability and photostability.